2008
DOI: 10.1001/archopht.126.6.826
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ω-3 Fatty Acid and Fish Intake in the Primary Prevention of Age-Related Macular Degeneration

Abstract: To systematically review the evidence on dietary-3 fatty acid and fish intake in the primary prevention of age-related macular degeneration (AMD). Methods: Seven databases were systematically searched with no limits on publication year or language using standardized criteria. Randomized controlled trials and prospective cohort, case-control, and cross-sectional studies were included. Of 2754 abstracts identified, 3 prospective cohort, 3 case-control, and 3 cross-sectional studies met the criteria. Measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(148 citation statements)
references
References 54 publications
(83 reference statements)
3
134
1
1
Order By: Relevance
“…13 The AREDS study demonstrated that daily supplementation with antioxidant reduced the risk of developing advanced AMD by 25% at 5 y. Epidemiological studies have suggested a protective role of n-3 PUFAs for developing AMD. [37][38][39][40][41][42][95][96][97] Also, subgroup analysis from the Nutritional AMD Treatment 2 Study from 2013, revealed that high levels of n-3 PUFAs in red blood cells can prevent AMD progression. 98 To assess if antioxidants and n-3 PUFAs could induce additive effects, a second AREDS2 study was designed to evaluate if inclusion of n-3 PUFAs to the AREDS formulation further reduced the risk of progression to advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The AREDS study demonstrated that daily supplementation with antioxidant reduced the risk of developing advanced AMD by 25% at 5 y. Epidemiological studies have suggested a protective role of n-3 PUFAs for developing AMD. [37][38][39][40][41][42][95][96][97] Also, subgroup analysis from the Nutritional AMD Treatment 2 Study from 2013, revealed that high levels of n-3 PUFAs in red blood cells can prevent AMD progression. 98 To assess if antioxidants and n-3 PUFAs could induce additive effects, a second AREDS2 study was designed to evaluate if inclusion of n-3 PUFAs to the AREDS formulation further reduced the risk of progression to advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Epidemiological studies indicate an inverse correlation between dietary intake of fish and the risk of developing AMD. [37][38][39][40][41][42] The disease preventive effects of increased fish intake have been associated with the content of marine omega-3 polyunsaturated fatty acids (n-3 PUFAs). 43 Deficiency of n-3 PUFAs in photoreceptors is associated with the development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent meta-analysis also supported the protective role of omega-3 fatty acids supplementation 118 . It was reported that dietary intake of omega-3 fatty acids was associated with reduced risk of late AMD while fish consumption (at least twice a week) was associated with reduced risk of both early and late AMD.…”
Section: Omega-3 Long Chain Polyunsaturated Fatty Acidsmentioning
confidence: 81%
“…However, no significant evidence was provided in these studies [79][80][81]. A recent review of randomized controlled trials concluded that there was no sufficient evidence to support the role of increasing levels of dietary n-3 PUFA to prevent or slow the progression of AMD [82].…”
Section: Omega-3 and Omega-6 Pufamentioning
confidence: 99%